Design Flow 2.0, assessing experience during ideation with increased granularity: A proposed method. (November 2016) - Safin, Stéphane; Dorta, Tomás; Pierini, Davide; Kinayoglu, Gôkçe; Lesage, Annemarie
Abstract : This paper presents a new method to measure designers' experience during ideation, by using the technique of self-observation instrumented with a device and an original software. Based on the previous concept of Design Flow and the experience fluctuation model, the proposed procedure asks participants to rate their perceived challenge and skills at each moment of their ideation session while watching the video recording. The method aims at increasing granularity of Design Flow and reducing time of interviews, while retaining the ability to analyse the ideation activity as a whole, not just selected excerpts. After performing a validation test confirming its effectiveness, we conclude that this method is a fast and practical way to obtain continuous quantitative data about designers' experience that can be analysed and triangulated with other sources of data (e.g. verbal analysis). Highlights: New method to assess the designers' experience during ideation. Auto-confrontation interview instrumented by a device and original software. Collect data about perceived challenge and skills fast and reliable. Ability to analyse the activity as a whole, not just selected excerpts. More granularity in the assessment, allowing comparing different activities.